2016
DOI: 10.2320/matertrans.mi201501
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of As-Solidified Ti-Zr Binary Alloys for Biomedical Applications

Abstract: Young s modulus (E), shear modulus (G), bulk modulus (K) and Poisson s ratio (ν) of Ti-Zr binary alloys containing 20, 40, 50, 60, 70 and 80 at% Zr and component pure metals (Ti, Zr) prepared by arc-melting followed by solidi cation process were determined precisely by ultrasonic sound velocity measurements. X-ray diffraction analysis showed that all the as-solidi ed alloys and pure metals were with a single-phase structure of the hexagonal close-packed lattice (martensitically formed α

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…According to the authors, Ti-60Zr alloys present an elastic modulus of 89 GPa, with a relatively low shear modulus, 33 GPa. 39 Recently explored Ti-Zr-Ta ternary alloys close to this composition displayed an impressive yield strength, higher than 1 GPa. 40 The second region of interest is located at near 80% Ti.…”
Section: U C Cmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, Ti-60Zr alloys present an elastic modulus of 89 GPa, with a relatively low shear modulus, 33 GPa. 39 Recently explored Ti-Zr-Ta ternary alloys close to this composition displayed an impressive yield strength, higher than 1 GPa. 40 The second region of interest is located at near 80% Ti.…”
Section: U C Cmentioning
confidence: 99%
“…In a recent assessment, Shiraishi et al identified a minimum Young modulus for the Ti-Zr binary system close to this region. According to the authors, Ti-60Zr alloys present an elastic modulus of 89 GPa, with a relatively low shear modulus, 33 GPa . Recently explored Ti-Zr-Ta ternary alloys close to this composition displayed an impressive yield strength, higher than 1 GPa .…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…The observed misfit shows an increase in the lattice parameter a α″ from the expected value of 0.288 nm to the observed value of 0.298 nm, and a decrease in both b α″ and c α″ lattice parameters from 0.526 nm to 0.492 nm and 0.473 nm to 0.463 nm, respectively. These kinds of differences are observed in many other titanium-based alloys containing Nb [ 69 ], Zr [ 70 , 71 ], Ta [ 72 , 73 ], V [ 74 , 75 ] and Mo [ 67 , 74 ], all of which show a continuous variation of the network parameters with increasing concentration of dissolved elements.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zr-based Ti-60Zr (at.%) alloy exhibited the lowest Young's modulus in the Ti-Zr binary alloys. [68] Hisata et al [26d] investigated the microstructure of (Zr-Ti)-(0-8)Nb (at.%). The phase changes with increasing Nb content as follows: α′ → α″ + α′ + β → β + α″ → β.…”
Section: Dense Zr-alloysmentioning
confidence: 99%